2018
DOI: 10.1111/1475-6773.12842
|View full text |Cite
|
Sign up to set email alerts
|

Content of Care in 15,000 Sick Child Consultations in Nine Lower‐Income Countries

Abstract: Consultations for children in nine lower-income countries are brief and limited. A greater number of clinical actions was associated with caregiver knowledge and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
6
19
0
Order By: Relevance
“…Data were collected by trained observers, which could lead clinicians to behave differently (Hawthorne effect), and is subject to observer error. Other studies that removed the first observation from analysis found similar performance [36]. Hawthorne effect would bias our results upward, suggesting that actual practice may potentially be worse than observed here, thus strengthening the concern about pre-service education.…”
Section: Associate Clinicians Nurses/midwivessupporting
confidence: 60%
“…Data were collected by trained observers, which could lead clinicians to behave differently (Hawthorne effect), and is subject to observer error. Other studies that removed the first observation from analysis found similar performance [36]. Hawthorne effect would bias our results upward, suggesting that actual practice may potentially be worse than observed here, thus strengthening the concern about pre-service education.…”
Section: Associate Clinicians Nurses/midwivessupporting
confidence: 60%
“…These findings are important because getting HCWs to perform focused history and physical examinations continues to be a challenge. [16][17][18][19][20][21] This is not surprising, given the large patient burden and lack of support staff in most countries, but it can contribute to misdiagnosis and poor patient management. Given the time constraints faced by the typical HCW, future work in this area should continue to focus on training HCWs to perform rapid and focused history and physical examinations designed to quickly assess for evidence of severe disease and important secondary, nonmalaria diagnoses (such as pneumonia, bacterial sepsis, or a catastrophic abdominal event).…”
Section: Discussionmentioning
confidence: 99%
“…When there are fewer patients, pressure on health workers to perform quick consultations is less likely than in facilities with high caseloads [52]. However, some studies did not find any association between caseload and health workers' performance [52,53]. For instance, in Tanzania Maestad et al did not find an association between caseload and the level of effort providers invest per patient case (defined as all actions taken by the clinician to improve the quality of the diagnostic process).…”
Section: Discussionmentioning
confidence: 99%
“…When there are fewer patients, pressure on health workers to perform quick consultations is less likely than in facilities with high caseloads . However, some studies did not find any association between caseload and health workers’ performance . For instance, in Tanzania Mæstad et al .…”
Section: Discussionmentioning
confidence: 99%